2016
DOI: 10.1152/ajprenal.00281.2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary iron intake and chronic kidney disease on fibroblast growth factor 23 metabolism in wild-type and hepcidin knockout mice

Abstract: In the setting of normal kidney function, iron deficiency is associated with increased FGF23 production and cleavage, altering circulating FGF23 levels. Our objective was to determine how chronic kidney disease (CKD) and dietary iron intake affect FGF23 production and metabolism in wild-type (WT) and hepcidin knockout (HKO) mice. For 8 wk, the mice were fed diets that contained adenine (to induce CKD) or no adenine (control group), with either low-iron (4 ppm) or standard-iron (335 ppm) concentrations. The low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 49 publications
3
52
1
Order By: Relevance
“…In animal models of CKD, it has been shown that ID stimulates FGF23 production but also upregulates cleavage, which leads to increased levels of circulating cFGF23, but normal levels of iFGF23. 9,27,28 In humans, Wolf and colleagues showed that ID anemia is associated with normal iFGF23 but markedly elevated cFGF23 levels to an extent that is only seen in advanced CKD or in hereditary diseases of FGF23 overproduction. 14 Moreover, rapid correction of ID with different intravenous iron preparations reduced cFGF23 levels by approximately 80% within 24 hours, 14 consistent with ID as an important stimulus for elevated cFGF23 levels.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of CKD, it has been shown that ID stimulates FGF23 production but also upregulates cleavage, which leads to increased levels of circulating cFGF23, but normal levels of iFGF23. 9,27,28 In humans, Wolf and colleagues showed that ID anemia is associated with normal iFGF23 but markedly elevated cFGF23 levels to an extent that is only seen in advanced CKD or in hereditary diseases of FGF23 overproduction. 14 Moreover, rapid correction of ID with different intravenous iron preparations reduced cFGF23 levels by approximately 80% within 24 hours, 14 consistent with ID as an important stimulus for elevated cFGF23 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia, anaemia and iron deficiency are frequent sequelae in CKD . They were all identified as stimuli of FGF23 production . Iron deficiency not only increases FGF23 transcription but also its cleavage .…”
Section: Homeostatic Regulation Of Fgf23mentioning
confidence: 99%
“…They were all identified as stimuli of FGF23 production . Iron deficiency not only increases FGF23 transcription but also its cleavage . Interestingly, iron supplementation has been shown to increase or decrease FGF23 , possibly depending on whether the supplementation stronger affects FGF23 transcription or cleavage.…”
Section: Homeostatic Regulation Of Fgf23mentioning
confidence: 99%
“…Because of the nature of iron loss during hemodialysis sessions, the use of this type of phosphate binders appears reasonable in such condition since iron is dissociated from the binders and then absorbed in part from the intestine. Of note, iron deficiency and the subsequent anemia are associated with the elevation in plasma FGF23 concentrations [95,[144][145][146][147] and the upregulation of bone FGF23 mRNA expression (Table 4) [147,148]. An in vitro study also shows that osteocytes in the medium containing low iron produce greater FGF23 mRNA expression [149].…”
Section: Ckd Ratsmentioning
confidence: 99%